THE CALIBER OF ELECTRONIC REPOSITORY SERVICES AND THEIR INFLUENCE ON BENEFICIARY SATISFACTION: A SURVEY CONDUCTED IN IRAQI PUBLIC UNIVERSITIES - Omaima Hameed Aladilee (Jurnal Ekonomi, Bisnis dan Pendidikan, 2026)
The study aims to explore how beneficiary satisfaction is being driven by the service quality delivered by digital repositories. The independent variable (quality of digital repository services) was examined by the following characteristics: perceived service quality, information usability, information security, feedback and interaction, tool application, and user experience. The dependent factor, beneficiary satisfaction, was measured using the following categories: integrity; identity or connection/group membership (as used in Two-Step and Value Chain Benefit); structural assurance; performance expectations/reliability; ease of use; desire to reuse. The number of digital repositories examined in this study is a fraction of those associated with 11 public institutions in Iraq. Of the 13 universities, 292 faculty members were selected purposively. A questionnaire-based survey design was used to collect data from the research population. Data from the research sample were analysed using SPSS V28 and AMOS V26. This study concluded that the quality of service in digital repositories has a considerable influence on beneficiary satisfaction. Improving the efficiency of these services increases Beneficiary Satisfaction. This confirms the hypothesis, as a strong relationship has been found between service quality and beneficiary satisfaction. The study recommended that warehouse managers focus on data accuracy and continuous updates, while providing in-depth descriptions of materials to enhance user understanding. This will immediately improve the perceived quality of the information.